2014
DOI: 10.1371/journal.pone.0096907
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Activation and Intracellular HCV Load in Peripheral Blood Monocytes Isolated from HCV Monoinfected and HIV-HCV Coinfected Patients

Abstract: BackgroundDuring HCV infection, the activation status of peripheral blood monocytes and its impact on HCV replication are poorly understood. We hypothesized that a modified activation of peripheral blood monocytes in HIV-HCV coinfected compared to HCV monoinfected patients may contribute to different monocytes reservoirs of HCV replication.MethodsWe performed a case-control analysis involving HCV-infected patients with and without HIV coinfection. In peripheral blood mononuclear cells (PBMCs), peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
3
0
1
Order By: Relevance
“…In the current study, the PBMCs RNA was found to be highest among the highly positive (45.4%) patient group as compared with the low-positive patient group. This shows that the patients having high viral load at the start of treatment were at a greater risk of viral relapse as compared with patients having low titer of HCV-RNA, which is in conformity with previously reported studies (8,12). Immunocytochemical staining technique was previously reported by our group for the detection of nonstructural proteins in PBMCs of local population (31).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the PBMCs RNA was found to be highest among the highly positive (45.4%) patient group as compared with the low-positive patient group. This shows that the patients having high viral load at the start of treatment were at a greater risk of viral relapse as compared with patients having low titer of HCV-RNA, which is in conformity with previously reported studies (8,12). Immunocytochemical staining technique was previously reported by our group for the detection of nonstructural proteins in PBMCs of local population (31).…”
Section: Discussionsupporting
confidence: 91%
“…In another instance, role of CCL-2 has been shown in enhancing the replication of HIV-1 in PBMCs isolated from patients [ 58 ]. These monocyte subsets (CD14 ++ CD16 + and CD14 + CD16 ++ ) have been also reported in HCV infection demonstrating that CD16 + monocytes may play important role in viral diseases [ 59 , 60 ].…”
Section: Hiv-1 Infection Of Monocytes/macrophagesmentioning
confidence: 88%
“…Owing to these viruses sharing similar transmission routes, coinfections are common, especially among persons who inject drugs (PWID) (7,30,34). These viruses affect the immune system by increasing immune activation and causing changes to T cell subset distribution (7,8,12,14,27). Our previous research (14) and that of others (5,7,9,11,27) have shown the importance of CD4…”
mentioning
confidence: 99%